Engaging Tenth Grade Students: Enhancing Speaking Skills through Role Play Icebreakers - Riyadi, Sugeng; Suryawati, Sri Suci; Seroja, Dienni Ratna (Universitas Pamulang, 2024)
Engaging students in learning speaking skills is crucial for vocational school graduates, particularly in pharmacy classes at SMKS Al-Huda. This study aims to investigate the effectiveness of using role play icebreakers to enhance student interest and participation in speaking activities. Employing a qualitative descriptive approach, the research involved 23 tenth-grade pharmacy students at SMKS Al-Huda. Data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman's method, which includes data reduction, data presentation, and conclusion drawing. Findings indicate that role play cards significantly increase students' interest and confidence in speaking, as evidenced by their enthusiastic participation and improved speaking abilities. This research highlights the potential of innovative teaching methods like role play icebreakers to make language learning more engaging and effective for students.